Ex Situ Culturing Experiments Revealed Psychrophilic Hydrogentrophic Methanogenesis Being the Potential Dominant Methane-Producing Pathway in Subglacial Sediment in Larsemann Hills, Antarctic - Ma, Hongmei; Yan, Wenkai; Xiao, Xiang; Shi, Guitao; Li, Yuansheng; Sun, Bo; Dou, Yinke; Zhang, Yu (Frontiers in Microbiology, 2018)
It was recognized only recently that subglacial ecosystems support considerable methanogenic activity, thus significantly contributing the global methane production. However, only limited knowledge is available on the physiological characteristics of this kind of methanogenic community because of the technical constraints associated with sampling and cultivation under corresponding environmental conditions. To elucidate methanogenesis beneath the glacial margin in East Antarctic Ice Sheet, we took an integrated approach that included cultivation of microbes associated with the sediment samples in the lab and analysis of mcrA gene therein. After seven months of incubation, the highest rate of methanogenesis [398 (pmol/day)/gram] was observed at 1 °C on a supply of H2. The rates of methanogenesis were lower on acetate or unamended substrate than on H2. The rates on these two substrates increased when the temperature was raised. Methanomicrobiales predominated before and after prolonged incubation, regardless whether H2, acetate, or unamended substrate were the energy source. Therefore, it was inferred that psychrophilic hydrogenotrophic methanogenesis was the primary methane-producing pathway in the subglacial ecosystem we sampled. These findings highlight the effects of temperature and substrate on potential methanogenesis in the subglacial sediment of this area, and may help us for a better estimation on the Antarctica methane production in a changing climate.